2009
DOI: 10.1534/genetics.109.104984
|View full text |Cite
|
Sign up to set email alerts
|

Cis-regulatory Changes atFLOWERING LOCUS TMediate Natural Variation in Flowering Responses ofArabidopsis thaliana

Abstract: Flowering time, a critical adaptive trait, is modulated by several environmental cues. These external signals converge on a small set of genes that in turn mediate the flowering response. Mutant analysis and subsequent molecular studies have revealed that one of these integrator genes, FLOWERING LOCUS T (F T), responds to photoperiod and temperature cues, two environmental parameters that greatly influence flowering time. As the central player in the transition to flowering, the protein coding sequence of FT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 83 publications
6
119
1
Order By: Relevance
“…Notably, all of these previous findings involve cis-regulatory changes while our data suggest that changes in both expression and coding sequence of FT orthlologs were involved in the evolution of cultivated sunflower. Thus, our findings challenge the prediction that downstream genes like FT are more likely to exhibit regulatory variation (Schwartz et al 2009). The redundancy afforded by a recent history of duplication, the novel derived expression domain of HaFT1, or multifarious selection acting on multiple pleiotropic effects may have uniquely fostered a selective sweep on a structural change in this case (Blackman et al 2010); however, given the expansion of FT/TFL1 homolog numbers observed in other species (Carmel-Goren et al 2003;Faure et al 2007;Nishikawa et al 2007;Danilevskaya et al 2008;Igasaki et al 2008;Mimida et al 2009), similar results may soon be observed in additional systems.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Notably, all of these previous findings involve cis-regulatory changes while our data suggest that changes in both expression and coding sequence of FT orthlologs were involved in the evolution of cultivated sunflower. Thus, our findings challenge the prediction that downstream genes like FT are more likely to exhibit regulatory variation (Schwartz et al 2009). The redundancy afforded by a recent history of duplication, the novel derived expression domain of HaFT1, or multifarious selection acting on multiple pleiotropic effects may have uniquely fostered a selective sweep on a structural change in this case (Blackman et al 2010); however, given the expansion of FT/TFL1 homolog numbers observed in other species (Carmel-Goren et al 2003;Faure et al 2007;Nishikawa et al 2007;Danilevskaya et al 2008;Igasaki et al 2008;Mimida et al 2009), similar results may soon be observed in additional systems.…”
Section: Discussioncontrasting
confidence: 85%
“…Alleles of FT ortholog VRN3 in wheat and barley have noncoding variants that bypass a vernalization requirement for expression (Yan et al 2006). Finally, allelic variation in FT and TWIN SISTER OF FT has been associated with natural variation in flowering among A. thaliana accessions (Schwartz et al 2009;Atwell et al 2010;Brachi et al 2010). Notably, all of these previous findings involve cis-regulatory changes while our data suggest that changes in both expression and coding sequence of FT orthlologs were involved in the evolution of cultivated sunflower.…”
Section: Discussionsupporting
confidence: 57%
“…The discovery that bulb formation is induced by the downregulation of AcFT4 and the upregulation of AcFT1 in response to LD photoperiods provides the molecular tools to investigate the difference between SD-, intermediate-and LD onion varieties (note: unlike SD flowering that requires days to be shorter than a critical length for flowering, all onions bulb when the daylength is longer than a critical length). Molecular genetic analysis in a wide range of plants has revealed that sequence changes in components of the circadian clock [48][49][50][51] and downstream components 51 , including FT genes 52,53 , underlie the variation in daylength required to induce flowering. It is therefore likely that the adaptation of onions to bulb at the appropriate time in different latitudes involves similar mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors have been found to regulate its expression; it is through the action of these many factors that an incremental response to optimal environmental conditions can push or delay the floral transition (Schwartz et al, 2009 also stabilizes CO protein . Exactly how FKF1 stabilizes CO protein in the afternoon remains unknown.…”
Section: Ft Transcriptionmentioning
confidence: 99%
“…The advent and streamlining of genomic editing techniques such as CRISPR/ CAS9 may make studying changes in transcription factor binding sites or important structural pieces of the DNA more feasible. In addition to studying these changes, additional insight into natural variation in the promoter sequences of FT or other floral integrator genes may shed light on differences in flowering time output that do not directly correlate with SNPs in coding regions of flowering time regulatory factors (Schwartz et al, 2009).…”
Section: Perspectivementioning
confidence: 99%